Prospects and Challenges to ICT Adoption in Teaching and Learning at Rural South African Universities: A Systematic Review - Sithole, Vikela Liso; Mbukanma, Ifeanyi (Research in Social Sciences and Technology, 2024)
This study aimed to systematically review the prospects and challenges associated with adopting Information and Communication Technology (ICT) in teaching and learning at rural universities in South Africa. To achieve this aim, a systematic review methodology was employed. The systematic review findings revealed a multifaceted landscape wherein opportunities for enhancing education through ICT exist alongside significant challenges. Prospects include the potential for technology to bridge educational gaps, increase accessibility, and provide innovative learning experiences. However, challenges such as inadequate infrastructure, limited connectivity, and varying levels of digital literacy pose significant impediments. The study emphasizes the need for targeted interventions to address these challenges, including infrastructure development, capacity building, and localized content creation. Additionally, recommendations for flexible learning models and collaborative partnerships are outlined to facilitate effective ICT adoption in the unique context of rural South African universities. Continuous research and evaluation are advocated to inform future strategies and ensure sustainable improvements in rural education through ICT integration.